Aminocarboxylic acids related to aspergillomarasmine A (AMA) and ethylenediamine-N, N′-disuccinic acid (EDDS) are strong zinc-binders and inhibitors of the metallo-beta-lactamase NDM-1. Issue 20 (12th February 2020) - Tehrani, Kamaleddin H. M. E.; Fu, Haigen; Brüchle, Nora C.; Mashayekhi, Vida; Prats Luján, Alejandro; van Haren, Matthijs J.; Poelarends, Gerrit J.; Martin, Nathaniel I.
Abstract : Aminocarboxylic acid analogues of aspergillomarasmine A (AMA) and ethylenediamine- N, N ′-disuccinic acid (EDDS) were prepared via a robust chemoenzymatic approach. These compounds display potent inhibition of the bacterial resistance enzyme NDM-1. Abstract : A series of aminocarboxylic acid analogues of aspergillomarasmine A (AMA) and ethylenediamine- N, N '-disuccinic acid (EDDS) were chemoenzymatically synthesized via the addition of various mono- and diamine substrates to fumaric acid catalyzed by the enzyme EDDS lyase. Many of these novel AMA and EDDS analogues demonstrate potent inhibition of the bacterial metallo-β-lactamase NDM-1. Isothermal titration calorimetry assays revealed a strong correlation between the inhibitory potency of the compounds and their ability to bind zinc. Compounds 1a (AMA), 1b (AMB), 5 (EDDS), followed by 1d and 8a, demonstrate the highest synergy with meropenem resensitizing an NDM-1 producing strain of E. coli to this important carbapenem of last resort.